2020
DOI: 10.53547/diegesis.v3i2.83
|View full text |Cite
|
Sign up to set email alerts
|

Tantangan dan Strategi Gereja Menjalankan Misi Allah dalam Menghadapi Penerapan Industri 4.0 di Indonesia

Abstract: Indonesia has begun to enter the Industrial 4.0 era. Preparation of resources must be started early to face this implementation. The adoption of Industry 4.0 causes significant changes in technology, ways of thinking, and social and economic structures. These changes will certainly affect the church in its main task of carrying out God's mission in Indonesia. The church must prepare from now on and not wait for the implementation of Industry 4.0 to affect the church. The purpose of this paper is to provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
4
0
4
Order By: Relevance
“…Hasil penelitian menyatakan bahwa misi Allah tetap sama namun dengan strategi yang tepat sehingga dapat diterapkan dalam melakukan misi di era revolusi Industri 4.0. (Purnomo & Sanjaya, 2020) Penelitian lainnya berupa analisis proses strategi manejemen keuangan yaitu perumusan strategi, mengembangkan visi dan misi, mengidentifikasi peluang dan ancaman. Bentuk penerapan strategi keuangan dengan mengelola aset gereja di GKE Resort Tewah dengan membangun sarang burung walet dan blok pasar.…”
Section: Pendahuluanunclassified
“…Hasil penelitian menyatakan bahwa misi Allah tetap sama namun dengan strategi yang tepat sehingga dapat diterapkan dalam melakukan misi di era revolusi Industri 4.0. (Purnomo & Sanjaya, 2020) Penelitian lainnya berupa analisis proses strategi manejemen keuangan yaitu perumusan strategi, mengembangkan visi dan misi, mengidentifikasi peluang dan ancaman. Bentuk penerapan strategi keuangan dengan mengelola aset gereja di GKE Resort Tewah dengan membangun sarang burung walet dan blok pasar.…”
Section: Pendahuluanunclassified
“…Purnomo and Sanjaya have measured that the church needs to clearly understand its position in the 21st century, given the impact of digitization on the church itself. [32] The fact that digitization will become a new ecosystem is a warning as to whether the church is changing or changing with digitization. It is where the role of theologians who are sucked into various components that move in God's church synergize and unite to continue to struggle and see through the eyes of Christ the birth of new humanist millennial leaders in digital civilization in the future.…”
Section: Theologians In Prophetic Contributions Give Birth To Humane ...mentioning
confidence: 99%
“…Aldrin and Yudhy revealed that digital media are very effective in this era with limited physical and environmental encounters. This era can provide teaching or discipleship opportunities through Internet media without direct face-to-face sessions [12]. The technological disruption era has provided many conveniences for various activities [13].…”
Section: Digital Media Potentials For Discipleship In the Disruption Eramentioning
confidence: 99%